1992
DOI: 10.1128/aem.58.5.1564-1568.1992
|View full text |Cite
|
Sign up to set email alerts
|

Use of polymerase chain reaction for detection of Listeria monocytogenes in food

Abstract: was used to analyze food for the presence of Listeria monocytogenes. Food samples were artificially contaminated to develop two procedures to detect the organism following enrichment steps. Procedure A was based on dilution of the enrichment broth followed by lysis of the bacteria and direct analysis of the lysate with PCR. With procedure A and artificially contaminated food samples, it was possible to detect fewer than 10 bacteria per 10 g of food. In procedure B, centrifugation was used to concentrate bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
2

Year Published

1994
1994
1999
1999

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(51 citation statements)
references
References 10 publications
3
46
0
2
Order By: Relevance
“…Thus a detection method based on PCR combines a high degree of specificity with a high degree of sensitivity. PCR technology has been successfully developed as a tool for specific and sensitive detection of micro-organisms in clinical samples (Hartskeer et al, 1989), environmental samples (Bej et al, 1991;Atlas et al, 1992), food or dairy samples (Harris & Griffiths, 1992;Niederhauser et al, 1992;Starbuck et al, 1992) and plant samples (Blakemore et at., 1992;Dong et al, 1992), In particular, food, milk and plant samples often contain components that significantly inhibit the polymerase chain reaction (Demeke & Adams, 1992;Rossen et al, 1992;Powell 6/a/., 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Thus a detection method based on PCR combines a high degree of specificity with a high degree of sensitivity. PCR technology has been successfully developed as a tool for specific and sensitive detection of micro-organisms in clinical samples (Hartskeer et al, 1989), environmental samples (Bej et al, 1991;Atlas et al, 1992), food or dairy samples (Harris & Griffiths, 1992;Niederhauser et al, 1992;Starbuck et al, 1992) and plant samples (Blakemore et at., 1992;Dong et al, 1992), In particular, food, milk and plant samples often contain components that significantly inhibit the polymerase chain reaction (Demeke & Adams, 1992;Rossen et al, 1992;Powell 6/a/., 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The virulence-associated genes mentioned above can be used as the target DNA for polymerase chain reaction (PCR). It is reported that prfA and hlyA are detected by PCR distinctively in L. monocytogenes suggesting the usefulness of PCR amplification of these genes for the identification of L. monocytogenes from various food samples (19,30 Listeria for humans, it is not known whether various L. monocytogenes strains exhibit a similar level of virulence. To determine the validity of PCR-based amplification of virulence-associated genes in the detection of virulent strains, we examined the actual virulence to mice in parallel with PCR amplification of each gene using various strains of L. monocytogenes and L. innocua.…”
mentioning
confidence: 99%
“…A 25-cm 2 area of each steak surface was swabbed with two sterile cotton swabs which were subsequently washed and expressed into a tube containing 10 mL sterile peptone water (0.1%). The tube was centrifuged at 100 ϫ g for 30 sec to sediment meat particles according to Neiderhauser et al (1992). The supernatant was transferred into a new tube and centrifuged at 3000 ϫ g for 30 min to pellet the bacterial cells.…”
Section: Fda Hydrolysismentioning
confidence: 99%